Remarkable anoxia tolerance by stoneflies from a floodplain aquifer - Rachel L. Malison; Bonnie K. Ellis; Amanda G. DelVecchia; Hailey Jacobson; Brian K. Hand; Gordon Luikart; H. Arthur Woods; Maribet Gamboa; Kozo Watanabe; Jack A. Stanford (Ecology, 2020)
Alluvial aquifers are key components of river floodplains and biodiversity worldwide, but they contain extreme environmental conditions and have limited sources of carbon for sustaining food webs. Despite this, they support abundant populations of aquifer stoneflies that have large proportions of their biomass carbon derived from methane. Methane is typically produced in freshwater ecosystems in anoxic conditions, while stoneflies (Order: Plecoptera) are thought to require highly oxygenated water. The potential importance of methane‐derived food resources raises the possibility that stonefly consumers have evolved anoxia‐resistant behaviors and physiologies. Here we tested the anoxic and hypoxic responses of 2,445 stonefly individuals in three aquifer species and nine benthic species. We conducted experimental trials in which we reduced oxygen levels, documented locomotor activity, and measured survival rates. Compared to surface‐dwelling benthic relatives, stoneflies from the alluvial aquifer on the Flathead River (Montana) performed better in hypoxic and anoxic conditions. Aquifer species sustained the ability to walk after 4–76 h of anoxia vs. 1 h for benthic species and survived on average three times longer than their benthic counterparts. Aquifer stoneflies also sustained aerobic respiration down to much lower levels of ambient oxygen. We show that aquifer taxa have gene sequences for hemocyanin, an oxygen transport respiratory protein, representing a possible mechanism for surviving low oxygen. This remarkable ability to perform well in low‐oxygen conditions is unique within the entire order of stoneflies (Plecoptera) and uncommon in other freshwater invertebrates. These results show that aquifer stoneflies can exploit rich carbon resources available in anoxic zones, which may explain their extraordinarily high abundance in gravel‐bed floodplain aquifers. These stoneflies are part of a novel food web contributing biodiversity to river floodplains.

Signatures of natural and unnatural selection: evidence from an immune system gene in African buffalo - K. E. Lane-deGraaf; S. J. Amish; F. Gardipee; A. Jolles; G. Luikart; V. O. Ezenwa (Conservation Genetics, 2015)

Lack of sex-biased dispersal promotes fine-scale genetic structure in alpine ungulates - Gretchen H. Roffler; Sandra L. Talbot; Gordon Luikart; George K. Sage; Kristy L. Pilgrim; Layne G. Adams; Michael K. Schwartz (Conservation Genetics, 2014)

CDFISH: an individual-based, spatially-explicit, landscape genetics simulator for aquatic species in complex riverscapes - Erin L. Landguth; C. C. Muhlfeld; G. Luikart (Conservation Genetics Resources, 2012)

High connectivity among argali sheep from Afghanistan and adjacent countries: Inferences from neutral and candidate gene microsatellites - G. Luikart; S. J. Amish; J. Winnie; A. Beja-Pereira; R. Godinho; F. W. Allendorf; R. B. Harris (Conservation Genetics, 2011)

Why replication is important in landscape genetics: American black bear in the Rocky Mountains - R. A. SHORT BULL; S. A. CUSHMAN; R. MACE; T. CHILTON; K. C. KENDALL; E. L. LANDGUTH; M.K. SCHWARTZ; K. MCKELVEY; FRED W. ALLENDORF; G. LUIKART (Molecular Ecology, 2011)
We investigated how landscape features influence gene flow of black bears by testing the relative support for 36 alternative landscape resistance hypotheses, including isolation by distance (IBD) in each of 12 study areas in the north central U.S. Rocky Mountains. The study areas all contained the same basic elements, but differed in extent of forest fragmentation, altitude, variation in elevation and road coverage. In all but one of the study areas, isolation by landscape resistance was more supported than IBD suggesting gene flow is likely influenced by elevation, forest cover, and roads. However, the landscape features influencing gene flow varied among study areas. Using subsets of loci usually gave models with the very similar landscape features influencing gene flow as with all loci, suggesting the landscape features influencing gene flow were correctly identified. To test if the cause of the variability of supported landscape features in study areas resulted from landscape differences among study areas, we conducted a limiting factor analysis. We found that features were supported in landscape models only when the features were highly variable. This is perhaps not surprising but suggests an important cautionary note – that if landscape features are not found to influence gene flow, researchers should not automatically conclude that the features are unimportant to the species’ movement and gene flow. Failure to investigate multiple study areas that have a range of variability in landscape features could cause misleading inferences about which landscape features generally limit gene flow. This could lead to potentially erroneous identification of corridors and barriers if models are transferred between areas with different landscape characteristics.

Species identification using a small nuclear gene fragment: application to sympatric wild carnivores from South-western Europe - R. Oliveira; D. Castro; R. Godinho; G. Luikart; P. C. Alves (Conservation Genetics, 2010)

A new individual‐based spatial approach for identifying genetic discontinuities in natural populations - S. MANEL; F. BERTHOUD; E. BELLEMAIN; M. GAUDEUL; G. LUIKART; J. E. SWENSON; L. P. WAITS; P. TABERLET; INTRABIODIV CONSORTIUM (Molecular Ecology, 2007)
The population concept is central in evolutionary and conservation biology, but identifying the boundaries of natural populations is often challenging. Here, we present a new approach for assessing spatial genetic structure without the a priori assumptions on the locations of populations made by adopting an individual‐centred approach. Our method is based on assignment tests applied in a moving window over an extensively sampled study area. For each individual, a spatially explicit probability surface is constructed, showing the estimated probability of finding its multilocus genotype across the landscape, and identifying putative migrants. Population boundaries are localized by estimating the mean slope of these probability surfaces over all individuals to identify areas with genetic discontinuities. The significance of the genetic discontinuities is assessed by permutation tests. This new approach has the potential to reveal cryptic population structure and to improve our ability to understand gene flow dynamics across landscapes. We illustrate our approach by simulations and by analysing two empirical datasets: microsatellite data of Ursus arctos in Scandinavia, and amplified fragment length polymorphism (AFLP) data of Rhododendron ferrugineum in the Alps.

Genetic diversity-fitness correlation revealed by microsatellite analyses in European alpine marmots (Marmota marmota) - A. Da Silva; G. Luikart; N. G. Yoccoz; A. Cohas; D. Allainé (Conservation Genetics, 2006)

Effects of a founder event and supplementary introductions on genetic variation in a captive breeding population of the endangered Spanish killifish - S. Schönhuth; G. Luikart; I. Doadrio (Journal of Fish Biology, 2003)
Twelve polymorphic allozyme loci were employed to assess the genetic change in a captive breeding population of the endangered killifish Aphanius baeticus in the Doñana National Park, south‐western Spain. The initial founder event did not significantly reduce the allelic richness or the expected heterozygosity. No genetic bottleneck signature was detected by tests for deviation from mutation‐drift equilibrium. The F ST between the wild source and captive population, however, was relatively high (0·053 or 0·122 when excluding or including the locus IDHP‐1 * respectively), after just two to three generations in captivity. Two generations after the incorporation of 68 new wild specimens (greater than five generations after founding) decreased the genetic differences and the F ST (0·041 excluding IDHP‐1 *). The restoration efforts appeared to be helpful and the study of 12 polymorphic loci and a sensitive parameter such as F ST were useful for monitoring genetic changes in captivity. Nonetheless, future monitoring should include additional highly polymorphic loci (microsatellites) to achieve higher power to detect genetic change. Such restoration and monitoring efforts should help to avoid rapid inbreeding, adaptation to captivity, and to maintain the long‐term evolutionary potential in small isolated populations.

Microsatellite DNA and recent statistical methods in wildlife conservation management: applications in Alpine ibex [ Capra ibex (ibex) ] - C. Maudet; C. Miller; B. Bassano; C. Breitenmoser‐Würsten; D. Gauthier; G. Obexer‐Ruff; J. Michallet; P. Taberlet; G. Luikart (Molecular Ecology, 2002)
We evaluated the usefulness of microsatellites and recently developed statistical methods for the conservation management of fragmented and reintroduced populations, using the alpine ibex ( Capra ibex ) as a model species. First, we assessed the effects of past reintroduction programmes on genetic diversity and population differentiation considering different population sizes and histories. We show that genetic variability in ibex populations ( H E ≈ 0.13) is among the lowest reported from microsatellites in mammal species, and that the Alpi Marittime–Mercantour population has suffered from a severe genetic bottleneck associated with its reintroduction. Second, using a computer‐simulation approach, we provide examples and rough guidelines for translocation programmes concerning the number and origin of individuals for future reintroductions and for the reinforcement of populations with low genetic variability. Finally, we use the ibex microsatellite data to assess the usefulness of several published statistical tests for detecting population bottlenecks and assigning individuals to their population of origin. This study illustrates that microsatellites allow: (i) evaluation of alternative translocation scenarios by simulating different numbers and origins of ‘migrants’; (ii) identification of bottlenecked populations (especially using the Wilcoxon signed‐ranks test); and (iii) population assignment with a high certainty ( P stucture or whichrun software).

Usefulness of molecular markers for detecting population bottlenecks via monitoring genetic change - G. LUIKART; W. B. SHERWIN; B. M. STEELE; F. W. ALLENDORF (Molecular Ecology, 1998)
It is important to detect population bottlenecks in threatened and managed species because bottlenecks can increase the risk of population extinction. Early detection is critical and can be facilitated by statistically powerful monitoring programs for detecting bottleneck‐induced genetic change. We used Monte Carlo computer simulations to evaluate the power of the following tests for detecting genetic changes caused by a severe reduction in a population's effective size ( N e ): a test for loss of heterozygosity, two tests for loss of alleles, two tests for change in the distribution of allele frequencies, and a test for small N e based on variance in allele frequencies (the ‘variance test’). The variance test was most powerful; it provided an 85% probability of detecting a bottleneck of size N e = 10 when monitoring five microsatellite loci and sampling 30 individuals both before and one generation after the bottleneck. The variance test was almost 10‐times more powerful than a commonly used test for loss of heterozygosity, and it allowed for detection of bottlenecks before 5% of a population's heterozygosity had been lost. The second most powerful tests were generally the tests for loss of alleles. However, these tests had reduced power for detecting genetic bottlenecks caused by skewed sex ratios. We provide guidelines for the number of loci and individuals needed to achieve high‐power tests when monitoring via the variance test. We also illustrate how the variance test performs when monitoring loci that have widely different allele frequency distributions as observed in five wild populations of mountain sheep ( Ovis canadensis ).

Characterization of microsatellite loci in the endangered long‐footed potoroo Potorous longipes - G. Luikart; J. Painter; R. H. Crozier; M. Westerman; W. B. Sherwin (Molecular Ecology, 1997)